Empowering Communities with Student-Led Technology Projects for Social Change - Pravista, Fedinda Nara Arsya (UM Purwokerto Press, 2025)
In this world, technology has become an indispensable tool for driving social change and community empowerment. And, when it comes to innovative ideas and fresh perspectives, students are often at the forefront of advancing new solutions. Student-led technology projects have emerged as a powerful means of creating impact and change within our communities. From implementing mobile apps and websites to harnessing the power of data analytics and artificial intelligence, students are leveraging technology in innovative ways to solve some of today's most pressing social issues. Through such projects, they learn valuable skills and gain experience that can propel their future careers. But, most importantly, student-led technology projects are empowering communities and creating sustainable change from within. By harnessing the passion and energy of our youth, we can make a lasting impact on society that transcends beyond the boundaries of our campuses.